Tumor microenvironment-activatable Fe-doxorubicin preloaded amorphous CaCO3 nanoformulation triggers ferroptosis in target tumor cells - Xue, Chen-Cheng (2020)
The rapid development of treatment resistance in tumors poses a technological bottleneck in clinical oncology. Ferroptosis is a form of regulated cell death with clinical translational potential, but the efficacy of ferroptosis-inducing agents is susceptible to many endogenous factors when administered alone, for which some cooperating mechanisms are urgently required. Here, we report an amorphous calcium carbonate (ACC)–based nanoassembly for tumor-targeted ferroptosis therapy, in which the totally degradable ACC substrate could synergize with the therapeutic interaction between doxorubicin (DOX) and Fe2+. The nanoplatform was simultaneously modified by dendrimers with metalloproteinase-2 (MMP-2)–sheddable PEG or targeting ligands, which offers the functional balance between circulation longevity and tumor-specific uptake. The therapeutic cargo could be released intracellularly in a self-regulated manner through acidity-triggered degradation of ACC, where DOX could amplify the ferroptosis effects of Fe2+ by producing H2O2. This nanoformulation has demonstrated potent ferroptosis efficacy and may offer clinical promise.